Assessment of head teachers’ stakeholder collaboration in church of Uganda founded secondary schools of Namirembe Diocese - Tumuhimbise, Jasper; Muweesi, Charles; Buluma, Alfred; Mbabazi, Faith; Ocheng, Kagoire Mary (International Journal of Educational Policy Research and Review, 2024)
This paper presents an assessment of head teachers’ stakeholder collaboration in church of Uganda founded secondary schools (CFSs) of Namirembe Diocese over the past five years (2019 to 2023). The purpose is to assess the effectiveness of stakeholder collaboration in schools, emphasizing their strength in school performance. This research employed a survey design utilizing a qualitative and quantitative descriptive approach. This was from eight out of twenty three CFSs in the Diocese. This included schools categorized as Government Aided (GA), USE, and Private. Respondents were staff, management, teachers, alumni and students. Data was collected through self-administered questionnaires. The final sample consisted of 211. The study evaluates the extent to which Head Teachers in CFSs have engaged with various stakeholders, on influencing performance of schools using a Likert Scale (1 is Strongly Disagree and 5 is Strongly agree). The stakeholders assessed include: Church related, Local and Central Governments, School Relations and Communities around from EE2 to EE17. Findings of this assessment reveal that stakeholder collaboration is significant for all except local parishes and alumni. It is recommended that Head Teachers should design a more integrated and supportive approaches in engaging them within CFSs. Further, for Head Teachers to put in place mechanisms for all stakeholders to be involved in decision making. Keywords: Stakeholder collaboration, leadership practices, Church of Uganda Founded Secondary Schools, Foundation Body
Article